Li Partitioning Into Coccoliths of Emiliania huxleyi: Evaluating the General Role of "Vital Effects" in Explaining Element Partitioning in Biogenic Carbonates. (7th August 2020) - Langer, Gerald; Sadekov, Aleksey; Greaves, Mervyn; Nehrke, Gernot; Probert, Ian; Misra, Sambuddha; Thoms, Silke
Abstract: Emiliania huxleyi cells were grown in artificial seawater of different Li and Ca concentrations and coccolith Li/Ca ratios determined. Coccolith Li/Ca ratios were positively correlated to seawater Li/Ca ratios only if the seawater Li concentration was changed, not if the seawater Ca concentration was changed. This Li partitioning pattern of E. huxleyi was previously also observed in the benthic foraminifer Amphistegina lessonii and inorganically precipitated calcite. We argue that Li partitioning in both E. huxleyi and A. lessonii is dominated by a coupled transmembrane transport of Li and Ca from seawater to the site of calcification. We present a refined version of a recently proposed transmembrane transport model for Li and Ca. The model assumes that Li and Ca enter the cell via Ca channels, the Li flux being dependent on the Ca flux. While the original model features a linear function to describe the experimental data, our refined version uses a power function, changing the stoichiometry of Li and Ca. The version presented here accurately predicts the observed dependence of D Li on seawater Li/Ca ratios. Our data demonstrate that minor element partitioning in calcifying organisms is partly mediated by biological processes even if the partitioning behavior of the calcifying organism is indistinguishable from that of inorganically precipitated calcium carbonate. Plain Language Summary: Marine shell‐forming organisms such as the minute, but abundant, coccolithophores (single‐celled phytoplankton) and foraminifera (single‐celled zooplankton) are not only ecologically important but also contribute significantly to the global carbonate sink. Minor elements (e.g., Sr and Li) trapped in biogenic carbonate sediments provide a window into past environmental conditions such as temperature, which is relevant for climate change. An understanding of elemental incorporation processes is required in order to correctly translate these minor element signatures into past environmental data. Here we conducted culture experiments with the coccolithophore Emiliania huxleyi to determine its Li incorporation behavior. We compare our results with previously published data on the foraminifer Amphistegina lessonii and data on synthetic calcite. The Li incorporation behavior of biogenic calcites is surprisingly similar to that of synthetic calcite. This is usually taken to mean that Li incorporation into shells should proceed inorganically. By contrast, we conclude that minor element incorporation processes in marine shell‐forming organisms always include biological processes. This is relevant to past climate reconstructions because it excludes any interpretation of minor element signatures in fossil shells based on inorganic processes only. Key Points: The Li partitioning pattern of E. huxleyi resembles that of A. lessonii and inorganic calcite Li partitioning in E. huxleyi is dominated by a coupled transmembrane transport of Li and Ca The vital effect is ubiquitous in calcifying organisms, even if it appears to be absent